Byron Lands in Korea: Translation and Literary/Cultural Changes in Early Twentieth‑Century Korea - Hyun, Theresa (TTR)

(untitled) (Association canadienne de traductologie, 1997)
AbstractByron Lands in Korea : Translation and Literary/Cultural Changes in Early Twentieth-Century Korea — This article deals with the role of translation during the formative phase of modern Korean poetry. Most scholars think that the work of poet/translators of the early twentieth century like Ch'oe Namson emphasized transmitting a message rather than technique. I assert that we need to re-examine the crucial relationship of the new poetic rhythms and images used by Ch'oe and the development of modern Korean poetic forms in the 1920s.